Review Note on Shifting Cultivation in Northeast India amidst Changing Perceptions - Bhuyan, Ratna (Dhaulagiri Journal of Sociology and Anthropology, 2019)
Historically, shifting cultivation has been traced back to the neolithic period. It has undergone transitions from being a subsistence agriculture to small surpluses. Despite the global changes intruding into the socio-economic sphere of the tribal communities across Northeastern region of India, shifting cultivation continues to play an important role in providing livelihoods and food security to the rural tribal households. It seems that shifting cultivation is closely tied to the cultural identity of the tribal people. Therefore, its importance lies beyond mere economic concerns. Though with government interventions and under innovative shifting cultivation, the farmers in the region have switched to newer methods of cultivation, shifting cultivation continues parallel to sedentary cultivation accommodating at the same time the value system and needs of the tribal society. Concurrently, the Jhumias – shifting cultivators are constantly incorporating new measures into shifting cultivation to make it ecologically less destructive. Amidst changing perceptions on shifting cultivation practices, the paper tries to analyse the continuance of shifting cultivation in the region.